A computational study of the insertion of Li, Na, and Mg atoms into Si(111) nanosheets - Manzhos, Sergei (2013)
Based on first principles calculations, we study the interaction of metal atoms (Li, Na, and Mg) with Si(111) nanosheets of different thicknesses. We show that the chemistry of the interactions is sensitive to both the nanosheet thickness and the dopant–surface distance. Both Li and Na atoms adsorb strongly on the nanosheet surface, accompanied by large charge transfers (∼0.9e) from the metal atoms to surrounding atoms. In contrast, Mg atoms have weak adsorption. Compared to bulk Si, we show that nanosheet Si is expected to improve the charge/discharge rate of Li/Na/Mg-ion batteries. Nevertheless, due to large insertion barriers (up to the prohibitive ∼2.1 and ∼3.1 eV for Mg and Na, respectively) and significant energy differences between surface and sub-surface sites (∼1.0 and ∼1.9 eV for Mg and Na, respectively), the theoretical capacities of Si for both Na-ion and Mg-ion batteries cannot be achieved at realistic charge/discharge rates.